Hypothesis and Theory: A Pathophysiological Concept of Stroke-Induced Acute Phase Response and Increased Intestinal Permeability Leading to Secondary Brain Damage - Ferrara, Fabienne; Zeisig, Vilia; Pietsch, Sören; Rütten, Rita; Dreyer, Antje Y.; Pieper, Laura; Schatzl, Ann-Kathrin; McLeod, Damian D.; Barthel, Henryk; Boltze, Johannes; Schrödl, Wieland; Nitzsche, Björn (Frontiers in Neuroscience, 2020)
Gut integrity impairment leading to increased intestinal permeability (IP) is hypothesized to be a trigger of critically illness. Approximately 15-20% of human ischemic stroke (IS) victims require intensive care, including patients with impaired level of consciousness or a high risk for developing life-threatening cerebral edema. Local and systemic inflammatory reactions are a major component of the IS pathophysiology and can significantly aggravate brain tissue damage. Intracerebral inflammatory processes following IS have been well studied. Until now, less is known about systemic inflammatory responses and IS consequences apart from a frequently observed post-IS immunosuppression. Here, we provide a hypothesis of a crosstalk between systemic acute phase response (APR), intestinal permeability (IP) and potential secondary brain damage during acute and subacute IS stages supported by preliminary experimental data. Alterations of the acute phase proteins (APPs) C-reactive protein and lipopolysaccharide-binding protein and serum level changes of antibodies directed against Escherichia (E.) coli-cell extract antigen (IgA-, IgM- and IgG-anti-E. coli) were investigated at 1, 2, and 7 days following IS in ten male sheep. We found an increase of both APPs as well as a decrease of all anti-E. coli antibodies within 48h following IS. This may indicate an early systemic APR and increased IP, and underlines the importance of the increasingly recognized gut-brain axis and of intestinal antigen release for systemic immune responses in acute and subacute stroke stages.